PENGAWASAN KEMITRAAN OLEH KPPU SEBAGAI UPAYA PENINGKATAN KESEJAHTERAAN UMKM - Febriano Ramadhan; Elfrida Ratnawati Gultom (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Since the KPPU has carried out partnership supervision, what has happened in the field has not been in line with the expectations set forth in the spirit of establishing the a quo Law. In 2021 KPPU handled 15 cases of partnership supervision, 13 of which came from reports made by the community and the remaining 2 were initiatives from KPPU. This indicates that of the many ongoing partnerships in Indonesia there are still violations committed by large companies against their partners. This research uses a legal approach, which is a type of legal research that examines a legal approach as an approach to legislation and regulation, in this case related to Law No. 20 of 2008. The conceptual approach is the same. Based on reports submitted to KPPU, there are still many business actors who partner with other larger business actors experiencing problems. Based on the explanation above, it can be concluded that: In the development of the national economy, MSMEs play an important role behind it, so it is necessary to strengthen MSMEs in carrying out their partnership relations. KPPU is a state institution appointed through Law 20/2008 to carry out partnership supervision. It is the right institution to carry out partnership supervision because it has the capacity and experience to do this.Keywords: Supervision, KPPU, Welfare, UMKM.